(untitled) (Global Journal of Management and Business Research, 2012)
Nigeria possesses most of the prerequisites for building a strong and vital economy. However, all this potentials cannot automatically transform the country into prosperous nation. Conscious efforts and policies are required to encourage and attract domestic and foreign investors to improve the competitiveness of a nation. Conscious efforts and policies are required to encourage and attract domestic and foreign investors to improve the competitiveness of a nation#x2019;s economic base. The study was set to analyze the Exchange Rate determinates in Nigeria (1971 #x2013; 2000). Six (6) variables were used in the exchange rate model namely: balance of payment, fiscal deficit, import tax, openness of the economy, trends and exports tax. Data on these variables were obtained largely from Central of Nigeria#x2019;s publication and empirically analyzed using econometric technique.